Implementasi Pendidikan Karakter di Sekolah Dasar Melalui Penguatan Kurikulum 2013 di Masa Pandemi Covid-19 - Hamna, Hamna; Windar, Windar (Program Studi PGSD Universitas Madako Tolitoli, 2022)
Character education through strengthening K-13 during the Covid-19 pandemic at SDN Sabang is still carried out in an online learning process. This research is a qualitative research. The results showed that the implementation of character education through strengthening the 2013 curriculum during the COVID-19 pandemic at SDN Sabang could be done well based on indicators, namely religious, namely praying before and after studying, greeting and celebrating holidays, honesty in doing assignments independently, telling the truth and being honest when finding items, being disciplined in participating in learning, collecting assignments on time, obeying rules and regulations, being independent, namely having the initiative to clean classrooms, solving problems on their own and keeping the environment clean, being responsible for receiving sanctions if they make mistakes, doing teacher orders, being able to work together